2011
DOI: 10.1039/c1an15017k
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of immunoassays with particles as labels: effect of antibody coupling using dendrimers as linkers

Abstract: Received 5 DOI:In this communication, we report on poly(amido amine) dendrimers (PAMAM) as coupling agents for recombinant single-chain (ScFv) antibodies to nanoparticle (NP) labels, for use in immunoassay. We present a simple theory for the kinetics of particle capture onto a surface by means of an antibody-antigen reaction, in which the important parameter is the fraction of the particle surface that is active for reaction. 10 We describe how increasing the generation number of the linking dendrimer signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 38 publications
3
36
0
Order By: Relevance
“…Changing chemical properties of the surfactants in the micelle, such as charge and packing, provide additional control over NP nucleation pathway and size [16,17]. Silica nanoparticles prepared using the microemulsion method are monodispersed and have been used extensively in immunoassays where they exhibit good reproducibility [16,18,19]. Furthermore, hydrophilic cancer drugs have been loaded into silica NPs for site-specific drug delivery in the treatment of tumour cells [20].…”
Section: Introductionmentioning
confidence: 99%
“…Changing chemical properties of the surfactants in the micelle, such as charge and packing, provide additional control over NP nucleation pathway and size [16,17]. Silica nanoparticles prepared using the microemulsion method are monodispersed and have been used extensively in immunoassays where they exhibit good reproducibility [16,18,19]. Furthermore, hydrophilic cancer drugs have been loaded into silica NPs for site-specific drug delivery in the treatment of tumour cells [20].…”
Section: Introductionmentioning
confidence: 99%
“…We have recently reported that fluorescent nanoparticles are very useful as labels in immunoassays to achieve improvements both in assay kinetics and sensitivity [7][8][9]. However, these particles typically have a negatively charged surface due to surfactants used to stabilize them and avoid aggregation [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…TIRF allows surfaceparticle interactions to be investigated, as it excites only particles within the evanescent field of the excitation light, providing surface specificity and improving signal to noise compared with conventional microscopy [5]. In this work, we use TIRF in a novel way to screen surfaces for the levels of non-specific binding in a particular system.We have recently reported that fluorescent nanoparticles are very useful as labels in immunoassays to achieve improvements both in assay kinetics and sensitivity [7][8][9]. However, these particles typically have a negatively charged surface due to surfactants used to stabilize them and avoid aggregation [10,11].…”
mentioning
confidence: 99%
“…ScFvshave also been tethered tonanoparticle labels via PAMAM dendrimers using amine coupling chemistry, with the scFv complex exhibiting an approximately four-fold higher signal to noise ratio than the dye-labelled scFv in immunoassays [165]. As discussed above (Section 3.2), the conjugation of anti-hen egg white lysozyme scFvs to NHS-activated poly(N-isopropylacrylamide) has been used to develop a novel strategy to achieve affinity separation of biomolecules in solution as opposed to on solid supports traditionally used in immunoaffinity chromatography applications [146].…”
Section: Amine Conjugationmentioning
confidence: 99%